A two-stage examination of business innovation decision-making: evidence from Ireland. (2015) - Bourke, Jane; Jordan, Declan
This paper explores business-level innovation decision-making by comparing the power of one-stage and two-stage models. A one-stage model represents the business making a one-off choice between four discrete innovation decisions. The two-stage model represents the business making an initial decision on whether or not to innovate, facilitating analysis of business innovation as simultaneous and sequential processes. This allows identification of the model which best explains innovation decision-making. Using original business-level survey data of over 400 SMEs in Ireland, results suggest that a two-stage model of the innovation decision has a statistically significant advantage in predicting innovation output, indicating the use of a two-stage model provides a better understanding of the impact of different knowledge sources on different types of innovation.